Board, Institusional Ownership and Firm Value - Winarsih Winarsih; Naila Najihah; Hendri Setyawan (Jurnal Telekomunikasi dan Informatika, 2024)
This study aims to explore the impact of board and institutional ownership on firm value, focusing on the property and real estate sector during 2020-2022. The independent variables of this study are board, independent board, and institutional ownership. Firm value is proxied by price book value. Sampling was carried out using the purposive sampling method and produced 177 sample data. Data analysis was carried out using PLS-SEM (Partial Least Squares-Structural Equation Modeling) with the help of WarpPLS 7.0 software. The results of the study indicate the influence of independent board and institutional ownership on firm value. However, the number of boards does not affect firm value. The implication of this study is the importance of supervision from independent and external parties to monitor firm value.